2017
DOI: 10.12659/msm.905814
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Dendritic Cell Vaccines and Avasimibe in Treatment of Head and Neck Cancer in Mice

Abstract: BackgroundThe main purpose of this study was to explore the antitumor effect and mechanisms of ACAT1 inhibitor combined with CSCs-DC vaccine.Material/MethodsWe isolated HNSCC CSCs and gained CSCs antigens, then used CSCs antigens to load dendritic cells (DC) and generated a CSCs-DC vaccine. We treated mice after surgical excision of established SCC7 tumors with CSCs-DC vaccine and/or ACAT1 inhibitor, and recorded local tumor relapse and host survival. T cells and B cells were harvested from mice treated with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In addition, avasimibe treatment effectively reduced regulatory T cell populations and enhanced the level of tumor‐infiltrating CD8+ T cell in a lung tumor model, while a combination of avasimibe with a Kras peptide vaccine further increased T cell immunity and improved inhibition of lung tumorigenesis 251 . CSCs‐DC vaccine combined with avasimibe was shown to have an enhanced therapeutic effect for head and neck cancer in a xenograft model 252 . In addition, treatment with an ACAT1 inhibitor can improve the antitumor efficacy of anti‐PD1 antibody therapy.…”
Section: Therapeutic Strategies Targeting Lipid Metabolism Reprogrammmentioning
confidence: 99%
“…In addition, avasimibe treatment effectively reduced regulatory T cell populations and enhanced the level of tumor‐infiltrating CD8+ T cell in a lung tumor model, while a combination of avasimibe with a Kras peptide vaccine further increased T cell immunity and improved inhibition of lung tumorigenesis 251 . CSCs‐DC vaccine combined with avasimibe was shown to have an enhanced therapeutic effect for head and neck cancer in a xenograft model 252 . In addition, treatment with an ACAT1 inhibitor can improve the antitumor efficacy of anti‐PD1 antibody therapy.…”
Section: Therapeutic Strategies Targeting Lipid Metabolism Reprogrammmentioning
confidence: 99%
“…Lung, head and neck cancer, melanoma models 87,115,129 HER2, receptor tyrosine-protein kinase ErbB-2; CRC, colorectal cancer.…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…Although avasimibe treatment effectively inhibits regulatory T cell populations and increases CD8 T cell infiltration in a lung tumour model, a combination of avasimibe with a Kras peptide vaccine has stronger tumour inhibitory effects 115 . Avasimibe can also be combined with a DC vaccine to boost adaptive anti-tumour immunity, as shown in a head and neck cancer model 129 . Finally, a combination of avasimibe with anti-PD-1 therapy effectively controls melanoma growth 87 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…Recent studies (3638) have also identified an association between ACAT-1 and the immune system, as inhibiting ACAT-1 expression may enhance the anti-tumor activity of cluster of differentiation (CD)8 + T cells. During T cell activation, lipid metabolism is required for membrane biosynthesis and cell growth.…”
Section: Discussionmentioning
confidence: 99%